Like Brother, Like Sister? The Importance of Family Background for Cognitive and Non-Cognitive Skills - Silke Anger; Daniel D. Schnitzlein (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper estimates sibling correlations in cognitive skills and non-cognitive skills to evaluate the importance of family background for skill formation. The study is based on a large representative German dataset, which includes IQ test scores and measures of personality (locus of control, reciprocity, Big Five) for brothers and sisters. Using a Restricted Maximum Likelihood (REML) model we find substantial influences of family background on the skills of both brothers and sisters. Sibling correlations of personality traits range from 0.24 to 0.59, indicating that even for the lowest estimate, one fourth of the variance can be attributed to factors shared by siblings. With one exception, all calculated sibling correlations in cognitive skills are higher than 0.50, indicating that more than half of the inequality can be explained by family characteristics. Comparing these findings to the results in the intergenerational skill transmission literature suggests that intergenerational correlations are only able to capture parts of the influence of the family on children s cognitive and non-cognitive skills. This result is in line with findings in the literature on educational and income mobility.
Keywords: J24; J62; I00; 330